Case Report: Suppression of Harem Stallion Behavior and Fertility Following Anti-Gonadotropin-Releasing Hormone Vaccination of a Captive Wild Przewalski's Horse (Equus ferus przewalskii) - Ponthier, Jérôme; Rigaux, Goulven; Parrilla-Hernandez, Sonia; Egyptien, Sophie; Gatez, Carine; Carrasco Leroy, Carla; Deleuze, Stéfan (Frontiers in Veterinary Science, 2020)
This report describes an option to modulate testicular function of wild horses and field methods to assess it. Non-surgical castration of a wild Przewalski stallion with anti-GnRH immunisation was performed by sub-cutaneous injection of 2 doses of 450g (3mL) of GnRH conjugated to diphtheria toxin, further repeated every six months. Semen quality was assessed after collection by electro-ejaculation under general anaesthesia. Endocrine and behavioural consequences were studied during a 2-year follow-up period. The procedure of electro-ejaculation was safe and effective to collect spermatozoa. Motility was low, but was improved by large dilution of sample after collection. Immuno-neutering resulted in a decrease of total sperm number and motility one month after primary vaccination. However, infertility could not yet be guaranteed. Six months post vaccination, serum testosterone concentrations had decreased and the treated stallion had lost his leader status in the band. Moreover, at the same time, total sperm number was near zero with no motile spermatozoa, and offspring was no longer observed. As a conclusion, electro-ejaculation under general anaesthesia is suitable on wild horses to obtain spermatozoa that should be washed or largely diluted before use for AI programs. Anti-GnRH immuno-neutering protocol led to a dramatic decrease of sperm number, motility and testosterone production. This also induced deep changes in leadership of the band. Such technique could be considered as an alternative to surgical castration in wild horses.